Performance of amidoxime-modified poly (Acrylonitrile-co-acrylic acid) for the removal of cadmium (II) and lead (II) ions in aqueous solution - Mohd Zahri, Nur Amirah (2015)
The untreated heavy metal ions that were discharged as effluent waste had caused serious impact on the environment and human health. The adsorption process is an alternative way to remove heavy metal ions. The polymer-based adsorbent was chosen as material to remove heavy metal ions due to its economic cost, can be prepared with convenient method and excellent capability to make high adsorption towards metal ions. In this study, the synthesis and modification of amidoxime (AO) modified poly(acrylonitrile-co-acrylic acid) (poly(ANco- AA)) was carried out. Next, the effect of adsorption parameters, equilibrium and kinetic studies of cadmium ion (Cd2+) and lead ion (Pb2+) were investigated. The optimisation of adsorption parameter was analysed using Response surface methodology (RSM). The poly(AN-co-AA) was synthesised via redox polymerisation and was further chemically modified with hydroxylamine hydrochloride to produce AO modified poly(AN-co-AA) as adsorbent. Then, single batch system of adsorption experiments for each heavy metal ions of Cd2+ and Pb2+ were implemented by varying the pH, adsorbent dosage, initial metal ion concentration and contact time. The isotherm and kinetic studies were carried out by using single batch of experimental data. Lastly, the optimisation of adsorption conditions was employed using Central composite design of RSM. The synthesis yield of poly(acrylonitrile) (PAN) was 73% and poly(AN-co-AA) 93:7 obtained the highest yield at 72%. The Fourier transform infrared (FTIR) spectra confirmed the successful of polymerisation due to the appearance of absorption peaks that were assigned to the C≡N and –COOH functional groups on the spectra. The microanalysis showed that the overall trend of elemental percentage for poly(AN-co-AA) copolymers were slightly decreased as the mole ratios of acrylic acid (AA) increased. The thermogravimetric (TG) analysis suggested that the thermal stability of poly(AN-co-AA) was lower as compared to the PAN. On the other hand, the FTIR spectra of AO modified poly(AN-co-AA) proved that the C≡N were successfully converted into amidoxime groups. The microanalysis showed that the increasing trend of nitrogen and hydrogen elements in amidoxime modified polymer. The amine capacity test confirmed the quantity of amidoxime functional groups in modified polymer. The maximum removal percentage based on parameters effect for each Cd2+ and Pb2+ were with an initial adsorbate concentration of 100 mg.L-1 at pH 9 with adsorbent dosage of 4 g.L-1 (Cd2+) and 8 g.L-1 (Pb2+). The Sips isotherms showed good agreement for the adsorption of Cd2+ (R2 of 0.9997) with maximum adsorption capacities of 20 mg.g-1. The adsorption of Pb2+ satisfied the Freundlich isotherms (R2 of 0.9875) with maximum adsorption capacities of 125 mg.g-1. The Lagergren pseudo-first order was observed to have better R2 compared to the other models for both Cd2+ and Pb2+. The RSM shows the removal of Cd2+ (98.33%) was satisfied with predicted value (98.58%) at optimum conditions, 10 mg.L-1 of Cd2+ initial concentration and the 4.66 g.L-1 of adsorbent dosage at pH 9.31. The removal of Pb2+ was 99.41% that fitted well with the predicted value (99.80%) with the optimum conditions, 20 mg.L-1 of Pb2+ initial concentration and 8.27 g.L-1 of adsorbent dosage at pH 9.08. The results suggested that the AO modified poly(AN-co-AA) sorbent is a potential material to capture high quantity of Cd2+ and Pb2+ from aqueous solution under certain conditions.